2008
DOI: 10.1111/j.1365-2966.2008.12925.x
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of primordial black holes in Jordan–Brans–Dicke cosmology

Abstract: We consider the evolution of primordial black holes in a generalized Jordan-Brans-Dicke cosmological model where both the Brans-Dicke scalar field and its coupling to gravity are dynamical functions determined from the evolution equations. The evaporation rate for the black holes is different from the case in standard cosmology. We show that the accretion of radiation can proceed effectively in the radiation-dominated era. It follows that the black hole lifetime shortens for low initial mass, but increases con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 58 publications
(91 reference statements)
0
18
0
Order By: Relevance
“…Also the accretion of dark energy onto the more general KerrNewman black hole was studied by Madrid et al [29] and Bhadra et al [30]. Till now, several authors [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] have discussed the accretion of various components of dark energy onto black holes. Recently, there has been a great interest in the study of dark-energy accretion onto a static wormhole [46][47][48].…”
Section: Introductionmentioning
confidence: 99%
“…Also the accretion of dark energy onto the more general KerrNewman black hole was studied by Madrid et al [29] and Bhadra et al [30]. Till now, several authors [31][32][33][34][35][36][37][38][39][40][41][42][43][44][45] have discussed the accretion of various components of dark energy onto black holes. Recently, there has been a great interest in the study of dark-energy accretion onto a static wormhole [46][47][48].…”
Section: Introductionmentioning
confidence: 99%
“…The lifetime for primordial black holes can be obtained in a scalar-tensor scenario, and is given by [27] t evap = t eq 1 − 5 3…”
Section: Scalar-tensor Cosmologymentioning
confidence: 99%
“…It was shown [27] that for a PBH with M i < (A/B) 1/4 to survive the radiation dominated era, one requires M i ≥ 10 13 M pl . It was shown [27] that for a PBH with M i < (A/B) 1/4 to survive the radiation dominated era, one requires M i ≥ 10 13 M pl .…”
Section: Scalar-tensor Cosmologymentioning
confidence: 99%
“…In recent papers [25,26], it is shown that the accretion of radiation prolongates the lifetime of PBHs. Now one can consider the accretion of radiation for this case also.…”
Section: B Scenario Bmentioning
confidence: 99%